A Computationally Efficient Multidiode Model for Optimizing the Front Grid of Multijunction Solar Cells under Concentration. (16th July 2020) - van de Stadt, Chris H.; Espinet Gonzalez, Pilar; Atwater, Harry A.; Saive, Rebecca
Abstract : We have developed a computationally efficient simulation model for the optimization of redirecting electrical front contacts for multijunction solar cells under concentration, and we present its validation by comparison with experimental literature results. The model allows for fast determination of the maximum achievable efficiency under a wide range of operating conditions and design parameters such as the contact finger redirecting capability, period and width of the fingers, the light concentration, and the metal and emitter sheet resistivity. At the example of a state-of-the-art four-junction concentrator solar cell, we apply our model to determine ideal operating conditions for front contacts with different light redirection capabilities. We find a 7% relative efficiency increase when enhancing the redirecting capabilities from 0% to 100%.